IMPLEMENTATION OF INFORMATION AND COMMUNICATION TECHNOLOGIES IN PRIMARY TRAINING IN BULGARIAN LANGUAGE AND LITERATURE - Vlaseva, T (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2019)
The aim of the study is to trace the dynamics in the transformation of the initial education in Bulgarian language and literature under the influence of information and communication technologies, to outline the problems and challenges of its development in the new digital age and possible ways for its closer integration with the new technologies. The subject of the study are the prerequisites, problems and perspectives for digital transformation of Bulgarian-language elementary education into ICT-based e-learning. Each of the three aspects of the study defines the tasks related to: 1) Discovering the prerequisites for integrating the new ICTs through retrospective analysis of their implementation, in particular in the initial Bulgarian language training, and thematic analysis of the curricula; 2) Analyzing the strengths and weaknesses in the functioning of ICT in the context of initial training; 3) Identify obstacles to ICT integration and identify priorities and perspectives for the digital transformation of the learning model.